Exploring research hotspots and future directions in neural tube defects field by bibliometric and bioinformatics analysis - Cao, Rui; Su, Yanbing; Li, Jianting; Ao, Ruifang; Xu, Xiangchao; Liang, Yuxiang; Liu, Zhizhen; Yu, Qi; Xie, Jun (Frontiers in Neuroscience, 2024)
Background: Neural tube defects (NTDs) is the most common birth defect of the central nervous system (CNS) which causes the death of almost 88000 people every year around the world. Much efforts have been made to investigate the reasons that contribute to NTD and explore new ways to for prevention.We trawl the past decade (2013-2022) published records in order to get a worldwide view about NTDs research field.Methods: 17,184 records about NTDs were retrieved from the Web of Science(WOS) database. Tools such as shell scripts, VOSviewer, SCImago Graphica, CiteSpace and PubTator were used for data analysis and visualization.Results: Over the past decade, the number of publications has maintained an upward trend, except for 2022. The United States is the country with the highest number of publications and also with the closest collaboration with other countries. Baylor College of Medicine has the closest collaboration with other institutions worldwide and also was the most prolific institution. In the field of NTDs, research focuses on molecular mechanisms such as genes and signaling pathways related to folate metabolism, neurogenic diseases caused by neural tube closure disorders such as myelomeningocele and spina bifida, and prevention and treatment such as folate supplementation and surgical procedures. Most NTDs related genes are related to development, cell projection parts, and molecular binding. These genes are mainly concentrated in cancer, wnt, MAPK, PI3K-Akt and other signaling pathways. The distribution of NTDs related SNPs on chromosomes 1, 3, 5, 11, 14 and 17 are relatively concentrated, which may be associated with high-risk of NTDs.